Prurigo in Children of Tropical Zone: Epidemiological, Clinical, and Etiological Characteristics in a Dermatology Department in Cotonou (Benin) - Bérénice Dégboé; Christiane Koudoukpo; Nina Maffo; Serge Otémé; Alida Kouassi; Fabrice Akpadjan; Nadège Agbéssi; Nadège Elégbédé-Adégbitè; Jojo Kalogama; Odile Houngbo; Hugues Adégbidi; Félix Atadokpèdé (Dermatology Research and Practice)
Introduction. The objective of this work is to document the epidemiological, clinical, and etiological features of prurigo in children. Methods. This is a descriptive and retrospective study done from January 2013 to September 2018 in the Dermatology Department of National and Teaching Hospital HKM of Cotonou. All children from 0–18 years diagnosed clinically with prurigo were the study sample. Visual analog scale was used to assess the severity of pruritus. The data were entered and analyzed with EpiData and Epi Info 7 software. Results. The prevalence of prurigo was 14.9% (234/1565) in the pediatric population. The mean age of the children at the onset of the disease was 5.4 years ± 4.9 years. Their sex ratio was 0.8. Pruritus was reported in 97.8% of cases; it was moderate in 50% and severe in 50%. Several phenotypes were described, including erosivo-crusted prurigo (36.3%) and papulo-vesicular prurigo (32%). Frequently observed clinical forms were chronic (44.4%), acute (38.9%), impetiginized (8.1%), and lichenified (4.3%). Prurigo predominated on the lower limbs (74.8%), upper limbs (47.9%), and buttocks and trunk (24.8% each). The main etiologies were prurigo strophulus (PS) (55.5%), scabiosis (20.5%), prurigo of Besnier (10.7%), and hookworm cutaneous larva migrans (HCLM) (8.5%). The PS was seasonal (p=0.036), while prurigo of Besnier, scabies, and HCLM were perennial. Conclusion. The main etiologies of prurigo in the study participants were PS, prurigo of Besnier, scabiosis, and HCLM. It affected with predilection the limbs of children of less than 5 years. Prurigo was almost always itchy and often evolved in an acute or chronic mode.